A negative electrode material and its preparation method and application
By using the use of silicon nitrogen deposits and carbon coating technology in the negative electrode material of lithium-ion battery to form the SI-N key and conductive network, the problem of poor conductivity and volume expansion of silicon materials has been solved, and the electrochemical properties and stability of the materials have sex.
Patent Information
- Application Number
- CN202411471377.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-10-22
AI Technical Summary
As the negative electrode material of lithium-ion batteries, silicon has poor conductivity, severe volume expansion, unstable solid electrolyte layer and irreversible capacity attenuation, which limits its application.
Through the method of silicon nitrogen, the SI-N key is formed in the porous carbon matrix to improve the electrical and inhibit the volume of the silicon, and then carry out carbon coverage in the nitrogen-containing atmosphere to build a conductive network to improve the speed of electronic transmission.
It significantly improves the conductivity and stability of silicon carbon composite materials, overcomes the problem of low silicon conductivity, and enhances the circulation stability of the material and electronic transmission efficiency.
Smart Images

Figure CN118993035B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of material technology, and in particular to a negative electrode material and a preparation method and application thereof. Background Art
[0002] At present, most of the negative electrode materials of lithium-ion batteries are graphite negative electrode materials, but graphite negative electrode materials can no longer meet current needs due to their low theoretical capacity limit (372mAh / g). Silicon materials are expected to become the negative electrode materials of the new generation of lithium-ion batteries due to their theoretical specific capacity of up to 4200mAh / g, low lithium insertion potential and low cost. However, silicon as a negative electrode material also has the following problems: First, during the process of lithium insertion and de-lithiation, there is a serious volume expansion, which makes the material easy to pulverize, fall off from the current collector and lose electrochemical properties. Second, an unstable solid electrolyte layer (solid electrolyte interface, SEI) is easily formed on the silicon surface, resulting in irreversible capacity decay. Third, silicon has poor conductivity and the capacity cannot be effectively released at high rates. These problems seriously limit the application of silicon negative electrode materials in lithium-ion batteries.
[0003] At present, the main means to reduce the expansion of silicon negative electrode materials are silicon particle nano-sizing and carbon layer coating. However, the silicon material itself has poor conductivity and the carbon layer coating is difficult to maintain its structural stability for a long time under the huge volume change of the silicon-based material.
[0004] The patent name is: A nano silicon-carbon composite material and its preparation method and application, and the publication number is: CN109167031A. It discloses a nano silicon-carbon composite material with a multi-level structure, with silicon nanoparticles as the core, amorphous carbon as the intermediate coating layer, and fluorinated carbon as the outer shell. This structure effectively improves the electrochemical performance of the material, but fluorine-containing substances are used in the process, and the production process is unsafe. The patent name is: A high-conductivity silicon-carbon negative electrode material and its preparation method, and the publication number is: CN117894951A. It discloses that a soft carbon layer is set on the pore wall of a porous hard carbon skeleton, nano silicon is deposited in the soft carbon layer, and a carbon coating layer is coated on the outside to obtain a silicon-carbon negative electrode material powder containing a carbon layer. Although this material improves the conductivity and rate performance of silicon-carbon materials to a certain extent, it is difficult to control the soft carbon layer during the preparation process, and its stability is poor during long cycles.
[0005] Therefore, it is urgent to develop a new type of silicon-carbon composite material to solve the above problems. Summary of the invention
[0006] The purpose of the present invention is to provide a negative electrode material and a preparation method and application thereof in view of the defects existing in the prior art. The preparation method forms Si-N bonds in a porous carbon matrix by silicon-nitrogen co-deposition, thereby improving the conductivity of the silicon-carbon composite material and inhibiting the volume expansion of silicon, thereby improving the stability of the material. Thereafter, carbon coating is performed in a nitrogen-containing atmosphere to obtain a nitrogen-doped carbon coating layer, which effectively constructs a conductive network, so that the prepared negative electrode material has better conductive properties, can effectively improve the electron transmission speed of silicon, and overcome the problem of low silicon conductivity.
[0007] To achieve the above objectives, in a first aspect, the present invention provides a method for preparing a negative electrode material, the preparation method comprising:
[0008] Step 1, under an inert atmosphere, introducing a mixed gas of a first silicon source gas, a nitrogen source gas and a first protective gas into a vapor deposition furnace, so that the first silicon source gas and the nitrogen source gas are vapor-deposited in a porous carbon matrix to obtain a first nitrogen-doped silicon-carbon composite material;
[0009] Step 2, introducing a mixed gas of a second silicon source gas and a second protective gas into a vapor deposition furnace, so that the second silicon source gas is deposited in the first nitrogen-doped silicon-carbon composite material to obtain a second nitrogen-doped silicon-carbon composite material;
[0010] Step 3, cycle the steps 1 and 2 several times;
[0011] Step 4, under an inert atmosphere, passing a mixed gas of a third protective gas and a carbon source gas into the vapor deposition furnace to passivate the second nitrogen-doped silicon-carbon composite material to obtain a passivated silicon-carbon composite material;
[0012] Step 5, carbon-coating the passivated silicon-carbon composite material with nitrogen to form a nitrogen-doped carbon coating layer, thereby obtaining the negative electrode material; in the negative electrode material, a conductive network is constructed by connecting the nitrogen in the carbon coating layer and the nitrogen in the silicon-carbon composite material inside the carbon coating layer.
[0013] Preferably, the passivated silicon-carbon composite material is coated with carbon containing nitrogen, specifically comprising:
[0014] In a nitrogen-containing atmosphere, a carbon source gas is introduced into the vapor deposition furnace to perform vapor deposition on the surface of the passivated silicon-carbon composite material;
[0015] Alternatively, the passivated silicon-carbon composite material and a solid carbon source are uniformly mixed in an organic solvent, and then spray-dried to obtain a powder, and then the powder is placed in a carbonization furnace to perform a carbonization treatment on the powder in a nitrogen-containing atmosphere;
[0016] Wherein, the carbon source gas includes: one or more of acetylene, ethylene, propylene, methane, and carbon dioxide; the solid carbon source includes: one or more of phenolic resin, epoxy resin, and melamine resin; the conditions of the carbonization treatment are: temperature 400°C-1000°C, time 2 hours-10 hours; the nitrogen-containing atmosphere includes: one or more of ammonia, nitric oxide, nitrogen dioxide, and nitrogen tetroxide.
[0017] Preferably, the particle size D50 of the porous carbon matrix is 3 μm-20 μm, the pore size is 1 nm-4 nm, and the micropores in the porous carbon matrix account for 10%-100%.
[0018] Preferably, the first silicon source gas includes: one or more of monosilane, disilane, chlorosilane, trichlorosilane gas, and silicon tetrachloride gas; the nitrogen source gas is one or more of ammonia, nitric oxide, nitrogen dioxide, and nitrogen tetroxide; the flow ratio of the first silicon source gas, the nitrogen source gas, and the first protective gas is 33:[2-8]:35.
[0019] Preferably, in step 1, the conditions for vapor deposition are: temperature 300° C.-700° C., time 10 min-160 min.
[0020] Preferably, the second silicon source gas includes: one or more of monosilane, disilane, chlorosilane, trichlorosilane gas, and silicon tetrachloride gas; and the flow ratio of the second silicon source gas to the second protective gas is [2-33]:35.
[0021] Preferably, in step 4, the carbon source gas includes one or more of acetylene, methane, and propylene.
[0022] In a second aspect, the present invention provides a negative electrode material, which is prepared by any preparation method described in the first aspect.
[0023] In a third aspect, the present invention provides a negative electrode plate, wherein the negative electrode plate comprises the negative electrode material described in the second aspect.
[0024] In a fourth aspect, the present invention provides a lithium-ion battery, wherein the lithium-ion battery comprises the negative electrode sheet described in the third aspect.
[0025] A method for preparing a negative electrode material provided by an embodiment of the present invention first generates Si-N bonds in a porous carbon matrix by co-deposition of silicon and nitrogen. The formation of Si-N bonds enhances the conductivity of the silicon-carbon composite material and inhibits the volume expansion of silicon, thereby improving the stability of the material. Nitrogen doping can provide more free electrons because nitrogen can act as an electron donor or acceptor to improve the conductivity of the silicon-carbon composite material. Nitrogen doping can also provide more active sites to provide sites for subsequent silicon deposition. Secondly, the capacity of the silicon-carbon composite material is increased by further silicon deposition. Finally, by forming a carbon coating layer containing nitrogen elements, on the one hand, the mechanical strength of the carbon coating layer is increased, which can more effectively buffer the pressure generated by the internal silicon expansion; on the other hand, the nitrogen in the carbon coating layer and the nitrogen in the silicon-carbon composite material inside the carbon coating layer strengthen the connection between the core layer of the negative electrode material and the outside, effectively constructing a conductive network, so that the negative electrode material has better conductivity, can effectively improve the electron transmission speed of silicon, and overcome the problem of low silicon conductivity. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 A flow chart of a method for preparing a negative electrode material provided by an embodiment of the present invention;
[0027] Figure 2 A schematic structural diagram of a negative electrode material provided in an embodiment of the present invention. DETAILED DESCRIPTION
[0028] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention will be further described in detail below with reference to the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0029] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments.
[0030] The present invention provides a method for preparing a negative electrode material, the process of which is as follows: Figure 1 As shown, the following steps are included:
[0031] Step 1, under an inert atmosphere, introducing a mixed gas of a first silicon source gas, a nitrogen source gas and a first protective gas into a vapor deposition furnace, so that the first silicon source gas and the nitrogen source gas are vapor deposited in the porous carbon matrix to obtain a first nitrogen-doped silicon-carbon composite material;
[0032] Specifically, under an inert atmosphere, the porous carbon matrix is first placed in a vapor deposition furnace, and then the vapor deposition furnace is heated. Among them, the inert atmosphere can be nitrogen and / or argon. The first silicon source gas can specifically include one or more of monosilane, disilane, chlorosilane, trichlorosilane gas, and silicon tetrachloride gas. The nitrogen source gas can be one or more of ammonia, nitric oxide, nitrogen dioxide, and nitrogen tetroxide. The first protective gas can be one or more of nitrogen, argon, and helium. Among them, the flow ratio of the first silicon source gas, the nitrogen source gas, and the first protective gas can be 33: [2-8]: 35, preferably 33: [4-6]: 35. The particle size D50 of the porous carbon matrix is specifically 3μm-20μm, the pore size is specifically 1nm-4nm, and the proportion of micropores in the porous carbon matrix is specifically 10%-100%. In the present application, the conditions for vapor deposition are in the same range, the temperature may be 300° C.-700° C., preferably 400° C.-600° C., and the time may be 10 min-160 min, preferably 90 min-150 min.
[0033] This step uses silicon source and nitrogen source for co-deposition. Nitrogen doping can provide more free electrons because nitrogen can act as an electron donor or acceptor, which improves the conductivity of the silicon-carbon composite material. Nitrogen doping can also provide more active sites for subsequent silicon deposition. When the silicon-carbon composite material is used in lithium batteries, it can increase the capacity of lithium batteries.
[0034] Step 2, introducing a mixed gas of a second silicon source gas and a second protective gas into a vapor deposition furnace, so that the second silicon source gas is deposited in the first nitrogen-doped silicon-carbon composite material to obtain a second nitrogen-doped silicon-carbon composite material;
[0035] Specifically, the second silicon source gas may include one or more of monosilane, disilane, chlorosilane, trichlorosilane gas, and silicon tetrachloride gas. The second protective gas may be one or more of nitrogen, argon, and helium. The flow ratio of the second silicon source gas to the second protective gas may be [2-33]:35, preferably [10-33]:35.
[0036] This step mainly involves silicon deposition, which can increase the capacity of the second nitrogen-doped silicon-carbon composite material.
[0037] Step 3, loop through steps 1 and 2 several times;
[0038] Specifically, the purpose of repeating the process several times is to ensure that silicon and nitrogen are fully deposited in the porous carbon matrix. The number of times may specifically be 2-6 times.
[0039] Step 4, under an inert atmosphere, passing a mixed gas of a third protective gas and a carbon source gas into a vapor deposition furnace to passivate the second nitrogen-doped silicon-carbon composite material to obtain a passivated silicon-carbon composite material;
[0040] Specifically, the inert atmosphere can be one or more of nitrogen, argon, and helium. The carbon source gas can specifically include one or more of acetylene, methane, and propylene. The third protective gas can be one or more of nitrogen, argon, and helium. The flow ratio of the third protective gas to the carbon source gas can be 35:[2-6], preferably 35:[4-5]. The passivation treatment time can be 1 hour to 3 hours, preferably 100 minutes to 2 hours. After the passivation treatment, a carbon layer will be formed on the surface of the second nitrogen-doped silicon-carbon composite material. The carbon layer can protect the material inside and improve the stability of the material.
[0041] Step 5: coating the passivated silicon-carbon composite material with carbon containing nitrogen to form a nitrogen-doped carbon coating layer, thereby obtaining a negative electrode material.
[0042] In the negative electrode material, a conductive network is constructed by connecting the nitrogen in the carbon coating layer and the nitrogen in the silicon-carbon composite material inside the carbon coating layer.
[0043] In the present application, carbon coating containing nitrogen elements is performed in the following two ways.
[0044] The first method is specifically: in a nitrogen-containing atmosphere, a carbon source gas is passed into a vapor deposition furnace, and vapor deposition is performed on the surface of the passivated silicon-carbon composite material. Among them, the nitrogen-containing atmosphere can be understood as a nitrogen-containing compound gas with strong activity. The nitrogen-containing atmosphere can specifically include one or more of ammonia, nitric oxide, nitrogen dioxide, and nitrogen tetroxide. The carbon source gas can specifically include one or more of acetylene, ethylene, propylene, methane, and carbon dioxide. The flow rate ratio of the carbon source gas and the nitrogen-containing compound gas can be 10: (1-3), wherein the flow rate of the carbon source gas can be 1L / min-50L / min, preferably 20L / min-40L / min. The temperature of the vapor deposition can be 300℃-700℃, preferably 400℃-600℃, and the time can be 10min-160min, preferably 90min-150min.
[0045] The second method of carbon coating is specifically: the passivated silicon-carbon composite material and the solid carbon source are mixed evenly in an organic solvent, and then spray-dried to obtain a powder, and then the powder is carbonized in a nitrogen atmosphere. The solid carbon source may specifically include: one or more of phenolic resin, epoxy resin, and melamine resin. The conditions for carbonization treatment may be: temperature 400°C-1000°C, preferably 500°C-800°C, time 2 hours-10 hours, preferably 4 hours-8 hours. The organic solvent may specifically include one or more of anhydrous ethanol, methanol, ethylene glycol, and acetone. The conditions for spray drying are: outlet temperature 130°C-200°C, preferably 150°C-180°C, pressure 3MPa-4MPa. The mass ratio of the passivated silicon-carbon composite material to the solid carbon source may be 10: [1-10], preferably 10: [1-5]. The mixing time may be 2 hours-24 hours, preferably 4 hours-20 hours.
[0046] The structure of the negative electrode material prepared by the above preparation method of the present invention is as follows Figure 2 As shown in , it can be seen that the interior of the negative electrode material is a porous carbon matrix and nano-silicon particles and nitrogen-doped nano-silicon particles deposited in the pores of the porous carbon matrix, and the exterior is a nitrogen-doped carbon coating layer.
[0047] The present invention performs carbon coating of nitrogen-containing elements on the silicon-carbon composite material, and the introduction of nitrogen doping makes the carbon coating layer have the following advantages:
[0048] First, nitrogen doping can change the surface chemical properties of carbon materials and increase their chemical stability. Nitrogen can form stronger covalent bonds, which helps to improve the durability of materials in electrochemical reactions. Second, the nitrogen-doped carbon coating can improve the electrochemical stability of negative electrode materials. Nitrogen can act as an electron donor or acceptor, which helps to stabilize the charge state on the surface of the negative electrode material and reduce the structural degradation of the negative electrode material during the charge and discharge process. Third, nitrogen doping can increase the mechanical strength of the carbon coating, making it more able to withstand the stress caused by volume expansion and contraction in electrochemical reactions. Fourth, the nitrogen-doped carbon coating can improve the interface stability between the negative electrode material and the electrolyte and reduce interfacial reactions. Therefore, the carbon coating of the present application can more effectively buffer the pressure generated by the internal silicon expansion, and even if it expands, it can be restored to its original state, effectively solving the various problems caused by the volume expansion of silicon as a negative electrode material.
[0049] In addition, for the overall negative electrode material system, nitrogen doping in the carbon coating and the internal silicon-carbon composite material can enhance electronic conductivity and improve the electron transmission capacity of the silicon-carbon composite material. Since there is a pathway between the nitrogen in the carbon coating and the nitrogen in the silicon-carbon composite material, a more effective conductive network can be formed, thereby changing the electrical properties of the porous carbon material, making the conductive path more continuous and reducing the transmission impedance of the electrons. This interconnected conductive network can significantly improve the overall electron transmission efficiency of the material and contribute to faster charging and discharging processes.
[0050] In summary, a method for preparing a negative electrode material provided by an embodiment of the present invention first generates Si-N bonds by co-deposition of silicon and nitrogen. The formation of Si-N bonds enhances the conductivity of the silicon-carbon composite material and inhibits the volume expansion of silicon, thereby improving the stability of the material. Nitrogen doping can provide more free electrons because nitrogen can act as an electron donor or acceptor to improve the conductivity of the silicon-carbon composite material. Nitrogen doping can also provide more active sites to provide sites for subsequent silicon deposition. Secondly, the capacity of the second nitrogen-doped silicon-carbon composite material is increased by further silicon deposition. Finally, by coating the silicon-carbon material with nitrogen-containing carbon to obtain a nitrogen-doped carbon coating layer, on the one hand, the mechanical strength of the carbon coating layer is increased, and the pressure generated by the internal silicon expansion can be more effectively buffered; on the other hand, the nitrogen in the carbon coating layer and the nitrogen in the silicon-carbon composite material inside the carbon coating layer strengthen the connection between the core layer of the negative electrode material and the outside, and effectively construct a conductive network, so that the negative electrode material has better conductivity, which can effectively improve the electron transmission speed of silicon and overcome the problem of low silicon conductivity.
[0051] The negative electrode material provided by the embodiment of the present invention can be applied to the electrode material of lithium ion batteries.
[0052] In order to better understand the technical solution provided by the present invention, the following uses a number of specific examples to illustrate the specific process of preparing the negative electrode material using the method provided by the above embodiment of the present invention, as well as the electrochemical properties of the prepared negative electrode material.
[0053] Example 1
[0054] In the first step, 5 kg of porous carbon matrix is placed in a vapor deposition furnace under a nitrogen atmosphere, and the vapor deposition furnace is heated to 500°C; then, a mixed gas of monosilane, ammonia and nitrogen is introduced into the vapor deposition furnace at a flow ratio of 33:2:35, and the ventilation is continued for 20 minutes, so that monosilane and ammonia are deposited in the porous carbon matrix to obtain the first nitrogen-doped silicon-carbon composite material.
[0055] In the second step, at 500° C., a mixed gas of monosilane and nitrogen with a flow ratio of 33:35 is introduced into a vapor deposition furnace and the ventilation is continued for 20 minutes, so that monosilane is deposited in the first nitrogen-doped silicon-carbon composite material to obtain a second nitrogen-doped silicon-carbon composite material.
[0056] Step 3: Repeat steps 1 and 2 twice.
[0057] In the fourth step, a mixed gas of nitrogen and acetylene is introduced into a vapor deposition furnace under a nitrogen atmosphere for 100 minutes to passivate the second nitrogen-doped silicon-carbon composite material to obtain a passivated silicon-carbon composite material, wherein the flow ratio of nitrogen to acetylene is 35:4.
[0058] In the fifth step, the passivated silicon-carbon composite material and the phenolic resin are stirred in anhydrous ethanol at a mass ratio of 10:1 for 4 hours to fully mix the passivated silicon-carbon composite material and the phenolic resin to obtain a mixed solution.
[0059] The sixth step is to spray dry the mixed solution to obtain powder. The spray drying conditions are temperature 150°C and pressure 3MPa.
[0060] In the seventh step, 1 kg of the powder was placed in a carbonization furnace under an ammonia atmosphere, and the temperature of the carbonization furnace was increased to 550°C at a heating rate of 5°C / min, and kept warm for 4 hours to obtain the negative electrode material, wherein the flow rate of ammonia was 5 L / min.
[0061] First, the conductivity of the negative electrode material was tested: 0.5 g of the negative electrode material was weighed and placed in a powder resistivity tester, and the conductivity was tested under a pressure of 20 MPa.
[0062] Afterwards, the prepared negative electrode material is used to prepare a pole piece of a lithium-ion battery, and the pole piece is used to assemble a button-type half-cell for testing, as follows:
[0063] First, the negative electrode material, acetylene black, and carboxymethyl cellulose (CMC) were added to deionized water in a mass ratio of 90:5:5 and mixed evenly. The slurry was prepared using a beater and coated on a copper foil current collector to obtain a pole piece, which was then dried in a vacuum drying oven at 85°C for 10 hours.
[0064] Secondly, the dried electrode was cut into 14 mm discs.
[0065] Then, the above-mentioned electrode pieces were assembled into a CR2032 button half-cell in an argon-filled glove box. The electrolyte of the CR2032 button half-cell was 1 mol / L lithium hexafluorophosphate LiPF6, and the solvent of the electrolyte was ethylene carbonate (EC), dimethyl carbonate (DMC) and diethyl carbonate (DEC), wherein the volume ratio of EC, DMC and DEC was 1:1:1. The counter electrode was a lithium sheet.
[0066] Finally, the CR2032 button half-cell was left to stand for 8 hours, and then the charge and discharge tests were performed on the Blue Power Battery Test System (CT2001A) at room temperature, as follows:
[0067] 1. Test the first-cycle expansion rate of the pole piece: At room temperature, cut the prepared pole piece through an ion beam, use a scanning electron microscope to photograph the cross section, and measure the thickness of the pole piece as T1, and measure the thickness of the copper foil current collector substrate as T2. Under the condition of 0.1C current density, the charging cut-off voltage is 2V, and the button half-cell is fully charged. Then disassemble the battery in the glove box, take out the pole piece, cut it through an ion beam, photograph the cross section again, and measure the thickness of the pole piece at this time, which is recorded as T3. Then calculate the first-cycle expansion rate, and the calculation formula is as follows:
[0068] First circle expansion rate = (T3-T1) / (T1-T2)×100%.
[0069] 2. Test the cycle capacity retention rate: the voltage window is 0.01V-2V, the discharge rate is 0.1C, the lower limit of the discharge voltage window is 0.01V, the number of cycles is 200, and the cycle capacity retention rate is tested.
[0070] Example 2
[0071] In the first step, 5 kg of porous carbon matrix is placed in a vapor deposition furnace under a nitrogen atmosphere, and the vapor deposition furnace is heated to 500°C; then a mixed gas of monosilane, ammonia and nitrogen is introduced into the vapor deposition furnace at a flow ratio of 33:5:35, and the ventilation is continued for 20 minutes, so that monosilane and ammonia are deposited in the porous carbon matrix to obtain the first nitrogen-doped silicon-carbon composite material.
[0072] The remaining steps and testing process are the same as in Example 1.
[0073] Example 3
[0074] The first step to the second step are the same as in Example 1.
[0075] Step 3: Repeat steps 1 and 2 four times.
[0076] The remaining steps and testing process are the same as in Example 1.
[0077] Example 4
[0078] The first to sixth steps are the same as in Example 1.
[0079] In the seventh step, 1 kg of the powder was placed in a carbonization furnace under an ammonia atmosphere, and the temperature of the carbonization furnace was increased to 600°C at a heating rate of 5°C / min, and kept warm for 4 hours to obtain the negative electrode material, wherein the flow rate of ammonia was 5 L / min.
[0080] The testing process is the same as in Example 1.
[0081] Example 5
[0082] The first to fourth steps are the same as in Example 1.
[0083] The fifth step is to introduce acetylene into a vapor deposition furnace under an ammonia atmosphere, and vapor deposit 1 kg of the passivated silicon-carbon composite material at 500°C for 100 minutes to form a nitrogen-doped carbon coating layer on the surface of the passivated silicon-carbon composite material, thereby obtaining a negative electrode material, wherein the flow rate of acetylene is 20 L / min, and the flow rate of ammonia is 2 L / min.
[0084] The testing process is the same as in Example 1.
[0085] Example 6
[0086] The first step to the second step are the same as in Example 1.
[0087] Step 3: Repeat steps 1 and 2 three times.
[0088] The remaining steps and testing process are the same as in Example 1.
[0089] Example 7
[0090] In the first step, 5 kg of porous carbon matrix is placed in a vapor deposition furnace under an argon atmosphere, and the vapor deposition furnace is heated to 400°C; then a mixed gas of disilane, nitric oxide and argon is introduced into the vapor deposition furnace at a flow ratio of 33:8:35, and the ventilation is continued for 10 minutes, so that disilane and nitric oxide are deposited in the porous carbon matrix to obtain the first nitrogen-doped silicon-carbon composite material.
[0091] In the second step, at 600° C., a mixed gas of disilane and argon with a flow ratio of 2:35 is introduced into a vapor deposition furnace and the aeration is continued for 100 minutes, so that the disilane is deposited in the first nitrogen-doped silicon-carbon composite material to obtain a second nitrogen-doped silicon-carbon composite material.
[0092] Step 3: Repeat steps 1 and 2 six times.
[0093] In the fourth step, a mixed gas of argon and methane is introduced into a vapor deposition furnace under an argon atmosphere for 2 hours to passivate the second nitrogen-doped silicon-carbon composite material to obtain a passivated silicon-carbon composite material, wherein the flow ratio of argon to methane is 35:2.
[0094] In the fifth step, the passivated silicon-carbon composite material and the epoxy resin are stirred in acetone at a mass ratio of 10:5 for 20 hours to fully mix the passivated silicon-carbon composite material and the epoxy resin to obtain a mixed solution.
[0095] The sixth step is to spray dry the mixed solution to obtain powder. The spray drying conditions are: temperature 180°C, pressure 4MPa.
[0096] In the seventh step, 2 kg of the powder is placed in a carbonization furnace under a nitric oxide atmosphere, and the carbonization furnace is heated to 400°C at a heating rate of 5°C / min, and kept warm for 8 hours to obtain the negative electrode material, wherein the flow rate of nitric oxide is 10 L / min.
[0097] Example 8
[0098] In the first step, 5 kg of porous carbon matrix is placed in a vapor deposition furnace under an argon atmosphere, and the vapor deposition furnace is heated to 600°C; then a mixed gas of chlorosilane, nitrogen dioxide and argon is introduced into the vapor deposition furnace at a flow ratio of 33:4:35, and the ventilation is continued for 90 minutes, so that chlorosilane and nitrogen dioxide are deposited in the porous carbon matrix to obtain the first nitrogen-doped silicon-carbon composite material.
[0099] In the second step, at 600° C., a mixed gas of chlorosilane and argon with a flow ratio of 18:35 is introduced into a vapor deposition furnace and the ventilation is continued for 160 minutes, so that chlorosilane is deposited in the first nitrogen-doped silicon-carbon composite material to obtain a second nitrogen-doped silicon-carbon composite material.
[0100] Step 3: Repeat steps 1 and 2 three times.
[0101] In the fourth step, a mixed gas of argon and propylene is introduced into a vapor deposition furnace under an argon atmosphere for 1 hour to passivate the second nitrogen-doped silicon-carbon composite material to obtain a passivated silicon-carbon composite material, wherein the flow ratio of argon and propylene is 35:6.
[0102] In the fifth step, the passivated silicon-carbon composite material and the epoxy resin are stirred in methanol at a mass ratio of 10:10 for 2 hours to fully mix the passivated silicon-carbon composite material and the epoxy resin to obtain a mixed solution.
[0103] The sixth step is to spray dry the mixed solution to obtain powder. The spray drying conditions are: temperature 130°C, pressure 4MPa.
[0104] In the seventh step, 2 kg of powder was placed in a carbonization furnace under a nitrogen dioxide atmosphere, and the temperature of the carbonization furnace was increased to 1000°C at a heating rate of 5°C / min, and kept warm for 2 hours to obtain the negative electrode material, wherein the flow rate of nitrogen dioxide was 10 L / min.
[0105] Example 9
[0106] In the first step, 5 kg of porous carbon matrix is placed in a vapor deposition furnace under a helium atmosphere, and the vapor deposition furnace is heated to 550°C; then, trichlorosilane gas, nitrogen tetroxide and helium mixed gas are introduced into the vapor deposition furnace at a flow ratio of 33:6:35, and the ventilation is continued for 50 minutes, so that the trichlorosilane gas and nitrogen tetroxide are deposited in the porous carbon matrix to obtain the first nitrogen-doped silicon-carbon composite material.
[0107] In the second step, at 600°C, a mixed gas of trichlorosilane gas and helium gas with a flow ratio of 24:35 is introduced into a vapor deposition furnace and the ventilation is continued for 150 minutes, so that the trichlorosilane gas is deposited in the first nitrogen-doped silicon-carbon composite material to obtain a second nitrogen-doped silicon-carbon composite material.
[0108] Step 3: Repeat steps 1 and 2 five times.
[0109] In the fourth step, a mixed gas of helium and acetylene is introduced into a vapor deposition furnace under a helium atmosphere for 3 hours to passivate the second nitrogen-doped silicon-carbon composite material to obtain a passivated silicon-carbon composite material, wherein the flow ratio of helium to acetylene is 35:4.
[0110] The fifth step is to introduce acetylene into a vapor deposition furnace under a nitrogen tetroxide atmosphere, and vapor deposit 1 kg of the passivated silicon-carbon composite material at 600°C for 120 minutes to form a nitrogen-doped carbon coating layer on the surface of the passivated silicon-carbon composite material, thereby obtaining a negative electrode material, wherein the flow rate of acetylene is 40 L / min, and the flow rate of nitrogen tetroxide is 8 L / min.
[0111] Example 10
[0112] In the first step, 5 kg of porous carbon matrix is placed in a vapor deposition furnace under a nitrogen atmosphere, and the vapor deposition furnace is heated to 450°C; then, a mixed gas of silicon tetrachloride gas, ammonia gas and nitrogen gas is introduced into the vapor deposition furnace at a flow ratio of 33:5:35, and the ventilation is continued for 80 minutes, so that the silicon tetrachloride gas and ammonia gas are deposited in the porous carbon matrix to obtain the first nitrogen-doped silicon-carbon composite material.
[0113] In the second step, at 450°C, a mixed gas of silicon tetrachloride gas and nitrogen gas with a flow ratio of 10:35 is introduced into a vapor deposition furnace and the ventilation is continued for 80 minutes, so that the silicon tetrachloride gas is deposited in the first nitrogen-doped silicon-carbon composite material to obtain a second nitrogen-doped silicon-carbon composite material.
[0114] Step 3: Repeat steps 1 and 2 four times.
[0115] In the fourth step, a mixed gas of nitrogen and methane is introduced into a vapor deposition furnace under a nitrogen atmosphere for 1.5 hours to passivate the second nitrogen-doped silicon-carbon composite material to obtain a passivated silicon-carbon composite material, wherein the flow ratio of nitrogen to methane is 35:5.
[0116] The fifth step is to introduce methane into a vapor deposition furnace under an ammonia atmosphere, and vapor deposit 1 kg of the passivated silicon-carbon composite material at 400°C for 160 minutes to form a nitrogen-doped carbon coating layer on the surface of the passivated silicon-carbon composite material, thereby obtaining a negative electrode material, wherein the flow rate of methane is 50 L / min, and the flow rate of ammonia is 15 L / min.
[0117] Comparative Example 1
[0118] In the first step, 5 kg of porous carbon matrix is placed in a vapor deposition furnace under a nitrogen atmosphere, and the vapor deposition furnace is heated to 500°C; then, a mixed gas of monosilane and nitrogen is introduced into the vapor deposition furnace at a flow ratio of 33:35, and the ventilation is continued for 20 minutes, so that monosilane is deposited in the porous carbon matrix to obtain the first nitrogen-free silicon-carbon composite material.
[0119] In the second step, at 500° C., a mixed gas of monosilane and nitrogen with a flow ratio of 33:35 is introduced into a vapor deposition furnace and the ventilation is continued for 20 minutes, so that monosilane is deposited in the first nitrogen-free doped silicon-carbon composite material to obtain a second nitrogen-free doped silicon-carbon composite material.
[0120] Step 3: Repeat steps 1 and 2 twice.
[0121] In the fourth step, a mixed gas of nitrogen and acetylene is introduced into a vapor deposition furnace under a nitrogen atmosphere for 100 minutes to passivate the second non-nitrogen-doped silicon-carbon composite material to obtain a passivated silicon-carbon composite material, wherein the flow ratio of nitrogen to acetylene is 35:4.
[0122] The remaining steps and testing process are the same as in Example 1.
[0123] Comparative Example 2
[0124] The first to sixth steps are the same as in Example 1.
[0125] The seventh step is to place 1 kg of powder in a carbonization furnace, heat the carbonization furnace to 550°C at a heating rate of 5°C / min, and keep it warm for 4 hours to obtain the negative electrode material.
[0126] The testing process is the same as in Example 1.
[0127] Comparative Example 3
[0128] In the first step, 5 kg of porous carbon matrix is placed in a vapor deposition furnace under a nitrogen atmosphere, and the vapor deposition furnace is heated to 500°C; then, a mixed gas of monosilane and nitrogen is introduced into the vapor deposition furnace at a flow ratio of 33:35, and the ventilation is continued for 20 minutes, so that monosilane is deposited in the porous carbon matrix to obtain the first nitrogen-free silicon-carbon composite material.
[0129] In the second step, at 500° C., a mixed gas of monosilane and nitrogen with a flow ratio of 33:35 is introduced into a vapor deposition furnace and the ventilation is continued for 20 minutes, so that monosilane is deposited in the first nitrogen-free doped silicon-carbon composite material to obtain a second nitrogen-free doped silicon-carbon composite material.
[0130] Step 3: Repeat steps 1 and 2 twice.
[0131] In the fourth step, a mixed gas of nitrogen and acetylene is introduced into a vapor deposition furnace under a nitrogen atmosphere for 100 minutes to passivate the second nitrogen-doped silicon-carbon composite material to obtain a passivated silicon-carbon composite material, wherein the flow ratio of nitrogen to acetylene is 35:4.
[0132] In the fifth step, the passivated silicon-carbon composite material and the phenolic resin are stirred in anhydrous ethanol at a mass ratio of 10:1 for 4 hours to fully mix the passivated silicon-carbon composite material and the phenolic resin to obtain a mixed solution.
[0133] The sixth step is to spray dry the mixed solution to obtain powder. The spray drying conditions are: temperature 150°C, pressure 3MPa.
[0134] In the seventh step, 1 kg of the powder was placed in a carbonization furnace, and the temperature of the carbonization furnace was increased to 550°C at a heating rate of 5°C / min, and kept at this temperature for 4 hours to obtain the negative electrode material.
[0135] The testing process is the same as in Example 1.
[0136] Comparative Example 4
[0137] The first step to the second step are the same as in Example 1.
[0138] The third step is to pass a mixed gas of nitrogen and acetylene into a vapor deposition furnace under a nitrogen atmosphere for 100 minutes to passivate the second nitrogen-doped silicon-carbon composite material to obtain a passivated silicon-carbon composite material, wherein the flow ratio of nitrogen to acetylene is 35:4.
[0139] In the fourth step, the passivated silicon-carbon composite material and the phenolic resin are stirred in anhydrous ethanol at a mass ratio of 10:1 for 4 hours to fully mix the passivated silicon-carbon composite material and the phenolic resin to obtain a mixed solution.
[0140] The fifth step is to spray dry the mixed solution to obtain powder. The spray drying conditions are temperature 150°C and pressure 3MPa.
[0141] The sixth step is to place 1 kg of the powder in a carbonization furnace under an ammonia atmosphere, heat the carbonization furnace to 550°C at a heating rate of 5°C / min, and keep it warm for 4 hours to obtain the negative electrode material, wherein the flow rate of ammonia is 5 L / min.
[0142] The testing process is the same as in Example 1.
[0143] Table 1 shows the electrochemical test results of the negative electrode materials of Examples 1-6 and Comparative Examples 1-4.
[0144]
[0145] Table 1
[0146] It can be seen from the data in Table 1 that the button-type half-cell assembled with the negative electrode material prepared by the preparation method of the present invention has significantly better cycle capacity retention rate, first cycle expansion rate and conductivity after 200 cycles than Comparative Examples 1-4. The reason is that the first nitrogen-doped silicon-carbon composite material formed by the co-deposition of the silicon source and the nitrogen source has a Si-N bond. The formation of the Si-N bond enhances the conductivity of the silicon-carbon composite material and inhibits the volume expansion of silicon, thereby improving the stability of the material. Therefore, the cycle capacity retention rate of the negative electrode material is high, and the nitrogen doping maintains the electrochemical properties of the silicon-carbon composite material while improving the conductivity of the silicon-carbon composite material. The nitrogen in the nitrogen-doped carbon coating layer and the nitrogen in the internal Si-N bond strengthen the connection between the core layer and the outside, effectively construct a conductive network, so that the negative electrode material has better conductivity, and can effectively improve the electron transmission speed of silicon. The nitrogen-doped carbon coating layer can effectively buffer the pressure generated by the internal silicon expansion, and can be restored to its original shape, effectively solving the problem of high silicon material expansion. Therefore, the first cycle expansion rate of the negative electrode material of the present application is relatively low. Moreover, through multiple cycles of step one and step two, the content of Si-N bonds can be adjusted. While enhancing the conductivity, the Si-N bonds can also isolate silicon particles and reduce the first-cycle expansion rate, making it have better cycle stability.
[0147] Using the Elimonta UNICUBE element analyzer in the CHNS analysis mode, 3 mg of the negative electrode material samples prepared in Example 1 and Comparative Examples 1-3 were taken to analyze the nitrogen content therein. The specific conditions were: the pressures of helium and oxygen (gas purity greater than 99.99%) were both 1200 mbar, the combustion tube temperature was set to 1150°C, the reduction tube temperature was set to 850°C, the helium flow rate was 200 mL / min, the oxygen flow rate was 15 mL / min, a thermal conductivity detector (TCD) was used, the detector temperature was 65°C, and after the detector was turned on, it was stabilized for 45 to 60 minutes. The test can be started after the baseline is stable (when there is no sample input, the analyzer reading or signal reaches a stable and repeatable state).
[0148] Test results: The nitrogen content of the negative electrode material in Example 1 is 2.33%. The nitrogen content of the negative electrode material in Comparative Example 1 is 0.83%, the nitrogen content of the negative electrode material in Comparative Example 2 is 1.34%, and the nitrogen content of the negative electrode material in Comparative Example 3 is 0.01%. It can be seen that nitrogen doping was successfully performed in the carbon coating layer in Example 1 of the present application. It should be noted that although nitrogen doping was not performed throughout the entire process of Comparative Example 3, there may be a small amount of nitrogen impurities in the porous carbon matrix or errors generated during the test, so trace amounts of nitrogen elements will be tested.
[0149] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A method for preparing a negative electrode material, characterized in that: The preparation method comprises: Step 1, under an inert atmosphere, introducing a mixed gas of a first silicon source gas, a nitrogen source gas and a first protective gas into a vapor deposition furnace, so that the first silicon source gas and the nitrogen source gas are vapor-deposited in a porous carbon matrix to obtain a first nitrogen-doped silicon-carbon composite material; Step 2, introducing a mixed gas of a second silicon source gas and a second protective gas into a vapor deposition furnace, so that the second silicon source gas is deposited in the first nitrogen-doped silicon-carbon composite material to obtain a second nitrogen-doped silicon-carbon composite material; Step 3, cycle the steps 1 and 2 several times; Step 4, under an inert atmosphere, passing a mixed gas of a third protective gas and a carbon source gas into the vapor deposition furnace to passivate the second nitrogen-doped silicon-carbon composite material to obtain a passivated silicon-carbon composite material; Step 5, coating the passivated silicon-carbon composite material with carbon containing nitrogen to form a nitrogen-doped carbon coating layer, thereby obtaining the negative electrode material; in the negative electrode material, a conductive network is constructed by connecting the nitrogen in the carbon coating layer and the nitrogen in the silicon-carbon composite material inside the carbon coating layer; Wherein, the carbon coating of the passivated silicon-carbon composite material with nitrogen-containing elements specifically includes: In a nitrogen-containing atmosphere, a carbon source gas is introduced into the vapor deposition furnace to perform vapor deposition on the surface of the passivated silicon-carbon composite material; Alternatively, the passivated silicon-carbon composite material and the solid carbon source are uniformly mixed in an organic solvent, and then spray-dried to obtain a powder, and then the powder is placed in a carbonization furnace and carbonized in a nitrogen-containing atmosphere.
2. The preparation method according to claim 1, characterized in that: The carbon source gas includes: one or more of acetylene, ethylene, propylene, methane, and carbon dioxide; the solid carbon source includes: one or more of phenolic resin, epoxy resin, and melamine resin; the conditions of the carbonization treatment are: temperature 400°C-1000°C, time 2 hours-10 hours; the nitrogen-containing atmosphere includes: one or more of ammonia, nitric oxide, nitrogen dioxide, and nitrogen tetroxide.
3. The preparation method according to claim 1, characterized in that: The particle size D50 of the porous carbon matrix is 3 μm-20 μm, the pore size is 1 nm-4 nm, and the micropores in the porous carbon matrix account for 10%-100%.
4. The preparation method according to claim 1, characterized in that: The first silicon source gas includes: one or more of monosilane, disilane, chlorosilane, trichlorosilane gas, and silicon tetrachloride gas; the nitrogen source gas is one or more of ammonia, nitric oxide, nitrogen dioxide, and nitrogen tetroxide; the flow ratio of the first silicon source gas, the nitrogen source gas, and the first protective gas is 33:[2-8]:
35.
5. The preparation method according to claim 1, characterized in that: In the step 1, the conditions for vapor deposition are: temperature 300° C.-700° C., time 10 min-160 min.
6. The preparation method according to claim 1, characterized in that: The second silicon source gas includes: one or more of monosilane, disilane, chlorosilane, trichlorosilane gas, and silicon tetrachloride gas; the flow ratio of the second silicon source gas to the second protective gas is [2-33]:
35.
7. The preparation method according to claim 1, characterized in that: In step 4, the carbon source gas includes one or more of acetylene, methane, and propylene.
8. A negative electrode material, characterized in that The negative electrode material is prepared by the preparation method described in any one of claims 1 to 7.
9. A negative electrode plate, characterized in that: The negative electrode sheet comprises the negative electrode material according to claim 8.
10. A lithium ion battery, characterized in that: The lithium-ion battery comprises the negative electrode sheet according to claim 9.
Citation Information
Patent Citations
A nano silicon-carbon composite material and a preparation method and application thereof
CN109167031A
High-conductivity silicon-carbon negative electrode material and preparation method thereof
CN117894951A
Silicon monoxide carbon negative electrode material for lithium ion battery and preparation method of silicon monoxide carbon negative electrode material
CN114613972A
Silicon-carbon negative electrode material, preparation method thereof and lithium ion battery
CN116799178A
Double-doped silicon-carbon composite material, preparation method, negative electrode material and lithium ion battery
CN117438564A